FAKTOR â FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL (Studi Pada Perusahaan Manufaktur yang Go Public di BEI 2007-2010 ) - Lasafeb Cahyo Sunu, 08.05.51.0006 (Students Journal of Economic and Management, 2014)
This research is a study to analyze the factors that affect the capital structure of the company manufactur Public Listed on the JSE in 2007-2010. This study examines and analyzes the effect of business risk, firm size , managerial ownership , and profitability of the capital structure. This research uses 84 observations that met the study criteria. The observations were then tested with normality, multikoleritas , autocorrelation and avoid violations of the classical assumptions. Regression testing result explain the relationship between variables . The results is a managerial ownership and influence in determining the profitability of the companyâs capital structure policy. This research has limitations that the sampling period is relatively short therefore, further research is suggested to extend the sampling period. Keywords : Business Risk, Company Size , Managerial Ownership , Profitability and Capital Structu